Comparative Proteomic Analysis of Rice Shoots Exposed to High Arsenate. Issue 10 (17th June 2013) - Liu, Yanli; Li, Ming; Han, Chao; Wu, Fengxia; Tu, Bingkun; Yang, Pingfang
Abstract Consumption of arsenic contaminated water and cereals is a serious threat to humans all over the world. Rice (Oryza sativa "Nipponbare"), as a main cereal crop, can accumulate arsenic more than 10‐fold that of in other cereals. To gain a comprehensive understanding of the response of rice subjected to 100 µM arsenate stress, a comparative proteomic analysis of rice shoots in combination with morphological and biochemical investigations have been performed in this study. The results demonstrated that arsenate suppressed the growth of rice seedlings, destroyed the cellular ultra‐structure and changed the homeostasis of reactive oxygen species. Moreover, a total of 38 differentially displayed proteins, which were mainly involved in metabolism, redox and protein‐metabolism, were identified. The data suggest the arsenic can inhibit rice growth through negatively affecting chloroplast structure and photosynthesis. In addition, upregulation of the proteins involved in redox and protein metabolism might help the rice to be resistant or tolerant to arsenic toxicity. In general, this study improves our understanding about the rice arsenic responsive mechanism.